PENGARUH TEKANAN PANAS DAN KEBISINGAN TERHADAP PERUBAHAN TEKANAN DARAH DAN DENYUT NADI PADA PEKERJA TEKSTIL DI PT. X PEKALONGAN - Suparyati . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
In  the  workplace,  there  are  several  factors  which  influence  the  work  environment  such  as  :physical  factors,  chemical  factors,  biological  factors  dan  psychologi  factors.  All  of  these  may interfere with the working environment and affect the health and safety. One source of danger of physical  environment  factors  in  the  workplace  is  a  heat  pressure  and  noise.  The  heat  pressure coming  from  the  roof  and  engine  production,  noisy  condition  is  caused  there  are  machines  that work  indoors  can  cause  physiological  disorders  that  changes  in  blood  pressure  and  pulse  on workers. Aim  of  this  research  was  to  analyze  of  differential  blood  pressure  and  pulse  of  worker  within production spinning yarn Department PT. X Pekalongan both before and after working. This  research  type  was  an  observational  research  Cross  Sectional  approach,  research  population were 196 persons by 46 person samples. Research result showed that heat pressure and noise within all of work location already exceeded limit  threshold  value.  There  were  differential  blood  pressure,  between  before  and  after  working. The  average  before  working  (systole  =  119,91  mmHg,  diastole  =75  mmHg)  higher  than  after worked  of  systole  value  (systole  =  107,82  mmHg,  diastole  =  67,39  mmHg)  respectively.  There were  dissimilarity  pulse  beat  before  and  after  working.  The  average  pulse  beat  before  worked (85,15 times/minute) less than after worked (99,15 times/minute). The p value of all experiments above is 0,000. There were no differential blood presussure and pulse beat from all work location based on heat pressure level and noise condition. Keywords: heat pressure, noise, blood pressure, pulse.